A GSD Estimation of the Relative Worth of Cover Crops in Cotton Production Systems - G. Grant Giesler (Journal of Agricultural and Resource Economics, 1993)
Cover crops can help reduce the negative environmental impacts of cotton production. Using time series yield data, this study utilizes generalized stochastic dominance to evaluate the relative worth, via risk premiums, of three cover crop and two conventional production systems based on expected net returns of each system and decision maker risk attitude. Results indicate, within the limitation of the study, two cover crop regimes possess a high degree of dominance over conventional systems. Determination of the dominant regime depends upon the risk attitude of a specific decision maker. This research suggests cover crop production systems may be feasible alternatives to conventional practices.